Shear strengthening of RC deep beams with large openings using carbon fiber reinforced polymers (CFRP) - Tong, Foo Sheng (2015)
This research deals with the experimental study of the behaviour of reinforced concrete deep beams with or without large rectangular openings as well as openings strengthened using externally bonded Carbon Fiber Reinforced Polymer (CFRP) composites in shear. The structural behaviour, including the load deflection, cracking patterns, failure mode, and effectiveness of the CFRP wraps were investigated. A total of four (4) specimens of beams with compressive strength of 35 MPa were tested to induce shear failure under 4 points loading test, which included one solid deep beam acted as a control beam (CB), one of which was tested without strengthening (US-BRO), and the remaining beams were strengthened with CFRP wraps in varying configurations around the opening (S-BRO-1, S-BRO-2). The beam had a cross section of 120 mm in width and 600 mm in depth as well as a length of 2400 mm. All the test specimens had a same geometry, main reinforcement arrangements and openings location. All the preparatory works of specimen materials were conducted in Laboratory FKASA. The examined parameter was the effect of configurations of the CFRP wraps used for the shear strengthening. The inclusion of un-strengthened large rectangular openings in the shear zone of a reinforced concrete deep beam leads to a reduction of ultimate beam strength by approximately 70%. The application of CFRP wraps with the presented strengthening configurations restricted the propagation of the diagonal crack and effectively increases ultimate load-carrying capacity as well as the ductility of the beam. The strength re-gains by U-shaped strengthening configuration around the openings was approximately 36% as compared to the beam with un-strengthened openings. However, the deep beam with U-shaped CFRP with horizontal fiber strengthened at the top and bottom chords of the openings were not capable to restore the control beam’s original structural strength remarkably. The beam only managed to re-gain about 41% of the control beam’s capacity.